A Discussion of the Power of Science to Complement Ethno+musicological Studies: Insights from Interdisciplinary Musicology (Revista História: Debates e Tendências, 2017)
In the animal kingdom, competition and hierarchical arrangements relative to members of the same sex are extremely common, with males competing for the top “alpha male” position and females ranked below them. Despite the widespread occurrence of hierarchical self-organization among animals and humans, ethno+musicologists often shy away from phylogenetic inferences and borrowing resources from biology, psychology, and anthropology. Is this a reflection of scholarly bias or a sense of unease with interdisciplinary, indirect, and large-scale data? This paper explores some answers to this question and suggests interdisciplinary connections for both ethnomusicology and musicology through the examination of biological and cultural frameworks with respect to social dominance.